Feasibility of Piezoelectric Endoscopic Transsphenoidal Craniotomy: A Cadaveric Study. (9th February 2014) - Tomazic, Peter Valentin; Gellner, Verena; Koele, Wolfgang; Hammer, Georg Philipp; Braun, Eva Maria; Gerstenberger, Claus; Clarici, Georg; Holl, Etienne; Braun, Hannes; Stammberger, Heinz; Mokry, Michael
Abstract : Objective . Endoscopic transsphenoidal approach has become the gold standard for surgical treatment of treating pituitary adenomas or other lesions in that area. Opening of bony skull base has been performed with burrs, chisels, and hammers or standard instruments like punches and circular top knives. The creation of primary bone flaps—as in external craniotomies—is difficult.The piezoelectric osteotomes used in the present study allows creating a bone flap for endoscopic transnasal approaches in certain areas. The aim of this study was to prove the feasibility of piezoelectric endoscopic transnasal craniotomies. Study Design . Cadaveric study. Methods . On cadaveric specimens (N = 5 ), a piezoelectric system with specially designed hardware for endonasal application was applied and endoscopic transsphenoidal craniotomies at the sellar floor, tuberculum sellae, and planum sphenoidale were performed up to a size of 3–5 cm 2 . Results . Bone flaps could be created without fracturing with the piezoosteotome and could be reimplanted. Endoscopic handling was unproblematic and time required was not exceeding standard procedures. Conclusion . In a cadaveric model, the piezoelectric endoscopic transsphenoidal craniotomy (PETC) is technically feasible. This technique allows the surgeon to create a bone flap in endoscopic transnasal approaches similar to existing standard transcranial craniotomies. Future trials will focus on skull base reconstruction using this bone flap.